Frontispiece: Bioactive nanomaterials for ion‐interference therapy (View 2/2020). Issue 2 (26th June 2020) - Liu, Yanyan; Zhang, Meng; Bu, Wenbo
Abstract : In article number 18, Wenbo Bu and co‐workers display that ions with biological actions participate in many important processes, including osmotic pressure and acid‐base balance maintenance, catalysis and signal pathway activation, protein and enzyme constitution, and biomolecule targeting. Their aberrant distribution/accumulation in cells may cause irreversible damage or the activation of biochemical reactions for cytotoxic ingredient generation, leading to cell death. This role of ions expedites a new tumour therapeutic modality, named ion‐interference therapy (IIT). Bioactive nanomaterials, not only successful targeting tumors but also sufficient release of active species, have attracted enormous interest in IIT due to their potential to tackle the challenges that are otherwise difficult for single ions or ion‐containing small molecules.